Environmental Performance with Firm Size as an Intervening Variable - Retnoningrum Hidayah; Indah Fajarini Sri Wahyuningrum; Dhini Suryandari; Trisni Suryarini; Heri Yanto; Rahayu Dinassari; Rita Rahayu (Universitas Diponegoro, 2022)
Environmental performance is significant in today's era. However, the high operational activity of the company has harmed the environment. This study examines the type of industry (TI) and the audit committee (AC) on environmental performance (EP). In addition, this paper uses firm size (FS) as an intervention. The research uses 198 units of analysis. The results show that the audit committee and firm size affected environmental performance. The type of industry and audit committee affect the firm size. Furthermore, firm size can mediate the relationship of the audit committee to environmental performance. However, the type of industry does not affect environmental performance. Therefore, firm size cannot mediate the relationship between the type of industry and environmental performance. Therefore, the company has to enhance the audit committee's role. Furthermore, the government should enforce regulations related to environmental performance, especially Law No. 32 of 2009 concerning the Protection and Management of the Environment, that all forms of environmental pollution carried out by individuals, corporations or officials can be subject to criminal sanctions. This study has limitations, only focusing on companies listed in the PROPER ranking. Future research could use all companies in many sectors for better interpretation.